Assessing the impact of foreign direct investments on export performance of Macedonia and Turkey - Bucevska, Vesna (Ss. Cyril and Methodius University in Skopje, Faculty of Economics-Skopje, 2014)
Export has been in the focus of economic literature for years due to its multi-fold contribution to the macroeconomic stability and economic growth. These contributions are of great importance for Macedonia and Turkey on their way to becoming full members of the European Union. The objective of this paper is to investigate empirically the impact of the inward foreign direct investments (FDI) on export performance of Macedonia and Turkey. To achieve this objective we use a popular model of export and estimate two models. The first (benchmark) model includes the real effective exchange rate, the potential GDP, trade liberalization and export in the previous year. Along with these explanatory variables, in the second model we include the FDI inflows variable. The results of the benchmark model indicate that trade liberalization has a positive and significant impact on export. The export performance is positively and significantly affected by the last year's exports. The estimated coefficient of real effective exchange rate is not statistically significant. The potential output has a positive impact on the increase of export but it is also statistically not significant. The results of the second model indicate that FDI have a positive impact on export performance of Macedonia and Turkey, but not significant. The other explanatory variables have kept their signs as in benchmark model and only trade liberalization and the export from the previous period remained statistically significant.
Keywords: foreign direct investments, export performance, generalized least squares